Avaliação da toxicidade e do trânsito gastrintestinal de extratos e frações nematicidas de Moringa oleifera em camundongos - Braga, Ana Carolina Linhares (2018)
Moringa oleifera is a plant with a high amount of molecules with related biological activities, attracting research to prove and justify its pharmacological use. As an example, the plant has been evaluated in the control of gastrointestinal nematodes in goats, parasites that cause production losses and available treatments (anthelmintics) trigger resistance in them. However, studies were lacking that evaluated the safety, the adequate dose and the actual gastrointestinal effects of fractions of the seeds of this plant with nematicidal activity. The objective of this study was to evaluate the acute, subchronic and gastrointestinal toxicity in mice of extracts and fractions of Moringa oleifera seeds with proven nematicidal activity. The crude aqueous extract (Exb) was produced from M. oleifera seeds with bark, lyophilized. To obtain the secondary compounds (C2) the EXB was fractionated with ethanol PA. After centrifugation the supernatant generated C2 and the pellet the protein fraction was fractionated by dialysis (D <12). The nematicidal potential was determined from the in vitro goat egg hatch test. For toxicological tests in mice, acute (single administration) and subchronic (administration for 14 days), the animals received different concentrations (5, 50, 300 mg / kg, with a dose of 2000 mg / kg in the test of acute toxicity) of the extract, D12, C2 or else distilled water (control group). At the end of the experiment, biochemical tests (creatinine, ALT and AST) and histological tests were performed. Gastric emptying test (EG) was performed to analyze the gastrointestinal transit. The treatments (Exb, D12 and C2) demonstrated high nematicidal potential with hatch inhibition rates higher than 93%. None of the experimental groups had evident toxicity with 100% survival rates both with single and repeated administration, serum levels of liver and kidney enzymes without statistical difference in control and histology without changes. In the EG test there was an increase in gastric retention only at the dose of 300 mg / kg of Exb and C2 treatments. The extract, D12 and C2 from M. Oleifera seeds, with proven nematicidal activity, showed no toxicity, showing high administration safety both in single and repeated doses and did not cause relevant gastrointestinal transit changes, thus justifying its pharmacological use.